2014
DOI: 10.3945/jn.113.176693
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Intake in Somalia Is Excessive and Associated with the Source of Household Drinking Water

Abstract: Few data on iodine status in Somalia are available, but it is assumed that deficiency is a public health problem due to the limited access to iodized salt. We aimed to describe the iodine status of the population of Somalia and to investigate possible determinants of iodine status. A national 2-stage, stratified household cluster survey was conducted in 2009 in the Northwest, Northeast, and South Central Zones of Somalia. Urinary iodine concentration (UIC) was determined in samples from women (aged 15–45 y) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 17 publications
2
60
2
1
Order By: Relevance
“…In the present investigation of this factor, it was found that the use of water of shallow wells or cisterns for drinking increased the risk of EII by 69%, but this association did not reach significance ( p > 0.05). While a survey in Somalia revealed that the excessive consumption of iodine was associated with the household drinking water source (42), this may be a more regionally specific characteristic, which needs further investigation in order to delineate the levels of iodine concentration from household drinking water sources.…”
Section: Discussionmentioning
confidence: 94%
“…In the present investigation of this factor, it was found that the use of water of shallow wells or cisterns for drinking increased the risk of EII by 69%, but this association did not reach significance ( p > 0.05). While a survey in Somalia revealed that the excessive consumption of iodine was associated with the household drinking water source (42), this may be a more regionally specific characteristic, which needs further investigation in order to delineate the levels of iodine concentration from household drinking water sources.…”
Section: Discussionmentioning
confidence: 94%
“…Makueni is a seasons region bordering the coast; most likely potentiating that water from wells and boreholes in the region are likely sources of iodine in water. A study undertaken in Somalia was suggestive that groundwater and surface iodine content is a potential determinant of dietary iodine [22].…”
Section: Discussionmentioning
confidence: 99%
“…Such iodine-rich drinking water has also been found in Somalia [21], Saharawi [22] and Europe [23]. The application of iodine-containing water-purification tablets is another source of excess iodine exposure from drinking water [24,25].…”
Section: Iodine: An Abundant and Easily Accessible Environmental Rmentioning
confidence: 99%